Study of intra-cranial space occupying lesion in children at tertiary care centre, Ahmedabad, Gujarat, India - Prajapati, Nisha (International Journal of Contemporary Pediatrics, 2017)
Background: ICSOL is some common children and leads to morbidity and mortality in the absence of early diagnosis and treatment2. Due to advance in diagnostic technique, the prognosis for children with ICSOL is more hopeful because of the development of newer therapeutic modalities. Objective of present study was to investigate the incidence, etiology, clinical manifestations, cilinico-radiological correlation, evaluate the therapeutic modalities and outcome of patients of ICSOL Methods: This prospective study was done among all 40 confirmed cases of space occupying lesion out of total 935 central nervous system related cases & 64 suspected cases admitted at department of peadiatrics in NHL medical college, Ahmedabad during July 2002 to October 2004. Results: Out of total CNS cases, 64 (6.8%) cases clinically diagnosed as SOLs cases and 40 (62.5%) were confirmed by radiological imaging technique. Study observed >50% cases in 5-9 age group and 57.5% male SOL. Tubeculoma covered highest (45.0%) cases and convulsion, headache, vomiting and altered sensorium were the main sign/symptoms. According to radiological findings, supratentorial SOL seen in 75.0% cases and mortality seen in 7.5% cases. Conclusions: Study observed higher incidence of SOL in the age group of 5 to 9 years. Total CNS cases were about 20.9% out of total admission and incidence of SOL was about 4.28% in total CNS cases. Highest incidence of tuberculoma which was most common etiology observed among both the gender. Study observed clinic-radiological correlation in SOL was about 62.5%. overall mortality in present in SOL was 7.5.